Profile of Problem-Solving Ability in Junior High School Students on Global Warming Lesson Material - M. Aldiono; Tarzan Purnomo; Tjipto Prastowo (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aims to determine the profile of problem-solving ability in junior high school students on global warming. Method: This research is preliminary. The study used a quantitative-descriptive research type and a purposive-sampling method. The instrument included a problem-solving ability test with four questions based on the Polya indicator on global warming lesson materials. The research sample consisted of 33 students from class VII-B, JHS Al-Miftah 4 Karang Anyar Ketapang Timur Sampang District East Java Province, who had previously received global warming lesson materials. The research data was analyzed by calculating the average score of the indicator student's problem-solving ability in the form of a percentage. Result: The results were as follows: the interpretation of problem-solving abilities in students is still dominant in the "Very Less" category with a score of 43%, and the overall average value of problem-solving abilities obtained based on indicators of problem-solving abilities gets of 32.25% belonging to the category "Not enough." Novelty: Analysis of problem-solving abilities can be a reference and a means of developing self-ability related to problem-solving abilities in the school environment, considering that solving abilities have yet to be highlighted too much, especially in remote areas. Problem-solving abilities are still a problem in the world of education, so further research is needed as a means to improve students' problem-solving abilities.